La flexibilité des enseignants d’EPS dans la gestion d’imprévus relationnels et organisationnels - Sarah Pochon; Nathalie Jelen (Éducation et Socialisation)
This article focuses on the professional gestures of two PE teachers working in the same REP+ establishment and when they face the unexpected (relational and organizational) lessons. Mobilizing a socio-didactic framework, the resultats show that the ways of adjusting to unforeseen events in the classroom respond to differentiated educational intentions. From the plural ressources mobilized by the two teachers, the survey shows that if the experiential dimension plays a role in the adjustments made in classe, this experiential judgment can be « wrong » sometimes and lead to limits of effectiveness in the adjustments adopted.